A simple real-time aerodynamic model for vehicles in overtaking situations. (1st January 2013) - Bruzelius, F.; Uystepruyst, D.; Jacobson, B.; Krajnović, S.
Aerodynamic forces and moments play an important role in overtaking situations and affect the trajectory of the involved vehicles. One method of studying these effects and how the driver responds to these is via driving simulator studies. However, models that describe aerodynamic forces and moments are typically computationally complex and not suited for real time execution in driving simulators. The present work presents a simplified real time model of the moments and forces acting in an overtaking situation due to aerodynamic pressure imbalances. The model is compared with experimentally validated Navier-Stokes solutions. Despite the model's simplicity, implemented as finite impulse response filters, it manages to capture the main features of the forces and moments. The approach used to derive the model is fairly general and might be used in similar applications where computational burden is a key issue.